Testicular Estrogen-Secreting Leydig Cell Tumor in 18F-FDG PET/CT: An Incidental Detection in a Patient Treated by Chemotherapy for Hodgkin Lymphoma. (January 2018) - Van Der Gucht, Axel; Maged, Zaher; Burruni, Rodolfo; Barras, Jean-Luc; Schaefer, Niklaus
Abstract : Abstract: We present images of a 50-year-old man who referred for treatment of a classic Hodgkin lymphoma. While 18 F-FDG PET/CT demonstrated a complete metabolic remission after chemotherapy, an increased 18 F-FDG uptake of a right testicular lesion in 18 F-FDG PET/CT and an unexplained bilateral gynecomastia were observed. A benign Leydig cell tumor was histopathologically proved after a right radical orchiectomy. The serum estradiol level was abnormally elevated reflecting the estrogen-secreting profile. This report highlights that a focal 18 F-FDG uptake in the testicular region with unexplained gynecomastia should suggest the diagnosis of an estrogen-secreting Leydig cell tumor on 18 F-FDG PET/CT.